2021
DOI: 10.3390/su13116401
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Financial Knowledge and Cashless Payment Behavior for Sustainable Development in Poland

Abstract: Financial knowledge is the main element of financial literacy, which is important for the sustainable development of individuals and society. Sustainability is a complex concept that spans many fields, including financial knowledge for all ages. Financial knowledge requires significant scientific research showing its impact on individuals and the economy, including non-cash payments. Consumer payment knowledge and its association with consumer financial behavior have long been a matter of widespread interest b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…When using mobile payment, consumers with more financial literacy tend to have a higher probability of understanding various risks in the mobile payment process, which may reduce the risk exposure and eventually improves their payment satisfaction (J€ unger and Mietzner, 2020;Souiden et al, 2020). On the contrary, consumers who lack financial knowledge can't utilize mobile payments to optimize their cashless payments, and may even be exposed to the risks brought by FinTech such as payment fraud caused by unreasonable high returns, which is not conducive to the improvement of payment satisfaction (Cojoianu et al, 2020;Swiecka et al, 2021). Therefore, the positive association between mobile payment use and payment satisfaction is stronger among consumers with higher financial literacy.…”
Section: The Association Between Mobile Payment Use and Payment Satis...mentioning
confidence: 99%
“…When using mobile payment, consumers with more financial literacy tend to have a higher probability of understanding various risks in the mobile payment process, which may reduce the risk exposure and eventually improves their payment satisfaction (J€ unger and Mietzner, 2020;Souiden et al, 2020). On the contrary, consumers who lack financial knowledge can't utilize mobile payments to optimize their cashless payments, and may even be exposed to the risks brought by FinTech such as payment fraud caused by unreasonable high returns, which is not conducive to the improvement of payment satisfaction (Cojoianu et al, 2020;Swiecka et al, 2021). Therefore, the positive association between mobile payment use and payment satisfaction is stronger among consumers with higher financial literacy.…”
Section: The Association Between Mobile Payment Use and Payment Satis...mentioning
confidence: 99%
“…Financial knowledge has a significant impact on household wealth. Financial knowledge is very important for individual financial decisions and depends to a large extent on their knowledge and understanding of their personal finances [47], just as an individual financial decision adopted level depends on financial knowledge, skills and attitudes [48].…”
Section: Bernheim and Garrett (2003)mentioning
confidence: 99%
“…It is argued that since knowledge is an important factor in comprehending financial technological solutions, it is crucial to understand how financial literacy influences the choice of payment among consumers (Swiecka, Terefenko, Wisniewski, & Xiao, 2021). Assessing the methods of payments in Canada, Henry et al (2017) reported that individuals who are more financially literate hold less cash and adopt more cashless methods of payments.…”
Section: Financial Literacy and Mode Of Payment Preferencesmentioning
confidence: 99%